2019
DOI: 10.1186/s12864-019-5968-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the NF-Y gene family in peach (Prunus persica L.)

Abstract: Background Nuclear Factor Y (NF-Y) is a heterotrimeric complex composed of three unique subunits: NF-YA, NF-YB, and NF-YC. The NF-Y transcription factor complex binds to the CCAAT box of eukaryotic promoters, playing a vital role in various biological processes in plants. However, the NF-Y gene family has not yet been reported from the peach genome. The current study identified and classified candidate peach NF-Y gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 49 publications
7
43
0
Order By: Relevance
“…Chromosomal distributions of the DGAT family genes showed that eight genes located on five different chromosomes both in buffalo and cattle. The family genes distributed on different chromosomes generally designated as segmental duplication events, and those co-located on the same chromosome are considered tandem duplication events [29]. Hence, both tandem and segmental duplication events have happened for the expansion of DGAT genes in the genome of buffalo and cattle.…”
Section: Collinearity Analysis Of Dgats In Buffalo and Cattlementioning
confidence: 99%
“…Chromosomal distributions of the DGAT family genes showed that eight genes located on five different chromosomes both in buffalo and cattle. The family genes distributed on different chromosomes generally designated as segmental duplication events, and those co-located on the same chromosome are considered tandem duplication events [29]. Hence, both tandem and segmental duplication events have happened for the expansion of DGAT genes in the genome of buffalo and cattle.…”
Section: Collinearity Analysis Of Dgats In Buffalo and Cattlementioning
confidence: 99%
“…To further elucidate the advantage of the proposed electrochemical immunosensor, the sensitivity and linear range of the immunosensor were compared with other CEA electrochemical immunosensors . The results are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Carbon‐based nanomaterials, such as: graphene oxide (GO) , carbon nanotubes (CNTs) , mesoporous carbon , carbon quantum dots , etc., have brought many tremendous achievements in immuno‐biosensors. Graphene oxide and carbon nanotubes, which are well known as promising precursors for carbon‐based nanomaterials, have great potential for use in immuno‐biosensors because of its unique characteristics such as facile surface modification , high mechanical strength , good biocompatibility and huge surface area . Up to now, many research studies demonstrated the usefulness of antibody immobilization and nanoscales‐based labelling probes of carbon‐based nanomaterials in immunosensors or immunoassays.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal distributions of the DGAT family genes showed that eight genes located on five different chromosomes both in buffalo and cattle. The family genes distributed on different chromosomes generally designated as segmental duplication events, and those co-located on the same chromosome are considered tandem duplication events [24]. Hence, both tandem and segmental duplication events have happened for the expansion of DGAT genes in the genome of buffalo and cattle.…”
Section: Collinearity Analysis Of Dgats In Buffalo and Cattlementioning
confidence: 99%